Strengthening of Reinforced Concrete Columns Using Recycled Polyethylene Terephthalate Fibers: A Preliminary Numerical Study - Dalgıç, Korhan Deniz; Dalgic, K.D.; Gozun, U.; Simsek, B.; Sencar, I.; Ispir, M.; Ilki, A. (fib. The International Federation for Structural Concrete, 2025)
Strengthening of reinforced concrete (RC) columns, which have inadequate capacities of deformation and axial/lateral load, using carbon fiber reinforced polymers (CFRP) has become widespread. However, concerns about cost, energy sustainability and environmental impact have led to increased interest in alternative fibers, such as recycled polyethylene terephthalate (PET) fibers, instead of high-tech, carbon-intensive materials. This study presents preliminary numerical analyses on the use of PET fibers recycled from tire industry waste in Türkiye to strengthen substandard RC columns. The numerical analyses of the column models were performed under axial and horizontal loads. The results show that even small amounts of PET-FRP fibers can significantly improve both lateral load and deformation capacities of RC column, indicating the development of strengthening strategies for upcoming column tests. Based on the results of numerical studies, an experimental program for quasistatic testing of substandard RC columns has been planned. © 2025 Elsevier B.V., All rights reserved.